ECONOMIC POLICY TARGETS: RELATIONSHIPS BETWEEN INFLATION RATES AND GDP GROWTH RATES IN OECD COUNTRIES IN 1990-2013 - Błaszczuk, Dariusz Jacek (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
There are always a few economic policy targets to be achieved at a given time. Politicians always strive to simultaneously achieve the optimal size for each of them. However, these targets are always at least partly contradictory. Therefore, striving to achieve an optimal level of individual targets does not lead to a stable, optimal long-term equilibrium. On the contrary, as the experiences of many countries show, whatever the number of targets, no optimal GDP rate and lack of political stability have been observed in the long run. This conclusion is supported by the results of theoretical analyses using the graphical and analytical methods of the rate of GDP as well as unemployment and inflation rates on the basis of the Okun’s law, the short-term Philips curve and the relationship between the rate of inflation and the rate of GDP. These three concepts are then combined into one model. Theoretical considerations lead to the conclusion that the target of long-term economic policy should be to maximise the rate of GDP growth while maintaining levels of other targets within specific limits. Ways to achieve this target in the long run, while maintaining political stability, are the appropriate impacts of policymakers on the relationships between every pair of targets. As a result, it is proposed (based on empirical data for the economy for a long enough period) to: - explore analytical forms and parameters of functions describing the relationships between all possible pairs of individual targets; - determine the empirical long-term equilibrium point (a combination of permissible individual economic policy targets): - directly, by solving the respective sets of equations, and, when this has no solution; - indirectly, on the basis of the indications of economic policymakers and theoreticians of various economic branches; - determine (in co-operation with politicians and theoreticians of various economic branches) the optimal combination of economic policy targets in the long run (the desired long-term equilibrium point), i.e.: the maximum growth rate of GDP and acceptable lower and upper bounds for all other targets; - determine the direction in which the empirical long-term equilibrium point should be moved in the near and further future to become the same as the desired long-term equilibrium point; - determine the factors in a given economy in a given period of time in the future that will move the long-term empirical equilibrium point in the desired direction, as well as the direction and strength of the influence of each of these factors; - implement by the policymakers the appropriate economic policy measures, i.e. to cause the replacement of the permissible combination of the individual targets of economic policy by the respective optimal combination (to influence the analytical forms and the parameters of functions describing the relationships between all pairs of individual targets, so that the rate of GDP would be the closest possible to its maximum value and at the same time boundary conditions for all other economic policy targets would be met). Of course, it is possible to depart slightly, in short periods, from maximising the rate of GDP growth in order to take into account any demand or supply shocks affecting other economic policy targets that may occur. The last step is always an assessment of the results of the economic policy by the voters. Theoretical considerations are complemented by an empirical analysis (based on quarterly data, separately for each OECD country) of the relationships between the rates of inflation and the growth rates of GDP during more or less the last two business Juglar cycles. An analysis of these relationships allows to construct "strategic groups’ maps" based on two criteria: the maximum GDP rates and the corresponding inflation rates. The analysis of these "maps" allows drawing preliminary proposals for economic policymakers. Further research (for individual OECD countries) will encompass empirical analyses of the investigations of the respective empirical long-term equilibria. The final result will be considerations on optimal economic policy measures for different countries based on results of the empirical studies.